Heart Concept: Reflections of Saint Theophan the Recluse in the context of the Russian religious philosophy of the XIX century. (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of the collective author's research of the concept of the heart in the philosophical and theological thought of St. the Recluse (G.V. Govorov), the largest figure of Russian culture of the XIX century. Pointing to a broad semantic context of religious and philosophical thought, in which the reflections of St. Theophan are immersed, the authors of the article turn to anthropologically oriented works - newly introduced into the scientific circulation of manuscripts—by archimandrite Evtikhian (Lestev), archbishop Luka (Voyno-Yasenetsky), S. N. Bulgakov, I. V. Kirievsky, A. S. Khomyakov, I. A. Ilyin, P. A. Florensky, B. P. Vysheslavtsev, and others dedicated to the philosophy of the heart. In this context St. Theophanes' position is characterized by a consistent practical appeal to the mystical-ascetic Christian tradition of the person seeking. According to the thought of St. Theophan, the conceptual and philosophical recognition of the heart as a symbol of the innermost being of the Russian soul implies its understanding as a symbolic instance of self-cognition ("human feeling"); keeping this instance in the horizon of self-cognition allows one to avoid the dualism of rationalistic and/or sensationalistic understanding of human nature. St. Theophan prefers a holistic, practical understanding of the fullness of human experience and its principled openness - up to dialogic appeal to the primordial image in the sympathetic identity of faith and truth, in the hope of finding answers to eternal questions related to the purpose and meaning of human existence. In the conclusion of the article, it is noted that the practical conceptualization of the heart, outlined by St. Theophan, remains relevant for modern philosophical and anthropological research in the era after postmodernism, when processes of return understanding of historically different anthropological paradigms were activated.